How are Joko Widodo Figures Framed on Instagram during Covid-19 Pandemic? A Framing Analysis - Rowinda Nicayana Simarmata; Arsen Nahum Pasaribu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This purpose of the study was  to find the types of framing analysis and the purposes used by Joko Widodo during pandemic Covid-19. This research used a qualitative descriptive approach and the data were taken from the captions text of Joko Widodo's Instagram. Robert Entman's theory is used to find the types and the purposes of the uses of framing analysis. The data showed that there were 220 identified data from 55 captions found in the posts May and June 2020 about Covid-19. The findings of the research were classified into framing categories; Defining Problematic Effects, Identifying Causes, Conveying Moral Judgment, and Endorsing Remedy. The results found that Instagram framed Joko Widodo about the Covid-19 problem in Indonesia, where the Defining Problematic Effect that often appeared was that in the midst of a pandemic the government and society still commemorated national days well even though virtually it happened because of the Identifying Causes of the Covid-19 pandemic which continues to be the reason for the obstruction of community and government activities, therefore the government always urges the public to maintain the discipline that is always displayed in his posts in Conveying Moral Judgment and the Endorsing Remedy that Joko Widodo often calls for is to ask the local government and other ranks. to maximize safety during the Covid-19 pandemic.